2013
DOI: 10.1371/journal.pone.0076245
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of a U-Type Antimicrobial Microemulsion System

Abstract: The structure-activity relationship of a U-type antimicrobial microemulsion system containing glycerol monolaurate and ethanol at a 1∶1 mass ratio as oil phase and Tween 20 as surfactant were investigated along a water dilution line at a ratio of 80∶20 mass% surfactant/oil phase, based on a pseudo-ternary phase diagram. The differential scanning calorimetry results showed that in the region of up to 33% water, all water molecules are confined to the hydrophilic core of the reverse micelles, leading to the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…At present, many studies on action mechanism of monoglyceride on bacterial cell membrane involve the change in physical morphology and the decrease in the ability to control material enter and exclude cell membrane (28, 50, 51). SEM images revealed that three monoglycerides exposure produced an uneven, rough and wrinkled surface as well as the appearance of depression on the affected E. coli cells, which was similar to the phenomenon reported in some literatures (21, 27, 50, 52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies on action mechanism of monoglyceride on bacterial cell membrane involve the change in physical morphology and the decrease in the ability to control material enter and exclude cell membrane (28, 50, 51). SEM images revealed that three monoglycerides exposure produced an uneven, rough and wrinkled surface as well as the appearance of depression on the affected E. coli cells, which was similar to the phenomenon reported in some literatures (21, 27, 50, 52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…DSC analysis was conducted on a Q200 differential scanning calorimeter (TA Instruments, New Castle, Delaware, U.S.A.) using our previously reported procedures [ 20 ]. Briefly, the microemulsion samples were carefully weighed into standard 40 μL aluminum pans and sealed immediately.…”
Section: Methodsmentioning
confidence: 99%
“…The dosage of GML in food products is not limited and its additive amount in food and health care products ranges from 10 to 2000 mg kg −1 (21 CFR GRAS 182.4505). In addition to its emulsification properties, GML also suppresses the growth and virulence of numerous bacteria, fungi, and enveloped viruses in vitro . For these reasons, GML are increasingly introduced into commonly consumed foods such as meat products, cereals, and soft beverage .…”
Section: Introductionmentioning
confidence: 99%